Efficacy of Stent Thrombectomy Alone or Combined With Intermediate Catheter Aspiration for Severe Cerebral Venous Sinus Thrombosis: A Case-Series - Peng, Tao; Dan, Bitang; Zhang, Zini; Zhu, Bifeng; Liu, Jianlin (Frontiers in Neurology, 2022)
Objective To assess the safety and efficacy of stent thrombectomy alone or combined with intermediate catheter aspiration for severe cerebral venous sinus thrombosis. Method We retrospectively collected the clinical data of 7 patients with severe CVST who received endovascular treatment at our hospital from January 2017 to June 2020. The patients had at least one adverse prognostic factor (mental status disorder, comatose state, intracerebral hemorrhage, or thrombosis of the deep venous system). Results The median age was 51 years. Three patients were women. Two or more venous sinuses were in involved in 5 patients. All patients received systemic anticoagulant therapy before endovascular therapy. Neurological deterioration was the main reason for patients with cerebral venous sinus thrombosis undergoing intravascular therapy. The median time from admission to intravascular therapy was 3 days (1–9 days). Primary endpoints: 6 patients (85.7%) had a modified Rankin scale score of 0 at day 90, and 1 patient (14.3%) had a modified Rankin scale score of 2 at day 90. Secondary endpoints: complete recanalization was achieved in 4 cases (57.1%) and partial recanalization in 3 cases (42.9%). Conclusion Stent thrombectomy, combined with intermediate catheter aspiration, balloon dilation, and regional thrombolysis/anticoagulation treatment, is an effective strategy to treat severe cerebral venous sinus thrombosis patients who had inadequate response to anticoagulant therapy. This strategy can quickly eliminate the occluded venous sinus and improve prognosis of severe cerebral venous sinus thrombosis.